Mass Refugee Inflow and Long-Run Prosperity: Lessons from the Greek Population Resettlement - Elie Murard; Seyhun Orcan Sakalli (Institute of Labor Economics (IZA), 2018)
This paper investigates the long-term consequences of mass refugee inflow on economic development by examining the effect of the first large-scale population resettlement in modern history. After the Greco-Turkish war of 1919–1922, 1.2 million Greek Orthodox were forcibly resettled from Turkey to Greece, increasing the Greek population by more than 20% within a few months. We build a novel geocoded dataset locating settlements of refugees across the universe of more than four thousand Greek municipalities that existed in Greece in 1920. Exploiting the spatial variation in the resettlement location, we find that localities with a greater share of refugees in 1923 have today higher earnings, higher levels of household wealth, greater educational attainment, as well as larger financial and manufacturing sectors. These results hold when comparing spatially contiguous municipalities with identical geographical features and are not driven by pre-settlement differences in initial level of development across localities. The long-run beneficial effects appear to arise from agglomeration economies generated by the large increase in the workforce, occupational specialization, as well as by new industrial know-hows brought by refugees, which fostered early industrialization and economic growth.
Keywords: O10; O43; N34; N44; 330; refugees; immigration; historical persistence; economic development